Survey on student's motivation in studying / Najwa Iman Nazari, Nur Najjah Mohamad Ramli and Noor Aqilah Hanie Asri - Nazari, Najwa Iman; Mohamad Ramli, Nur Najjah; Asri, Noor Aqilah Hanie (2020)
Humans need a balanced knowledge of their lives. Without knowledge, a country cannot produce a stable country. Therefore, motivation and inspiration are very important roles for the students. Motivation is the word derived from the word 'motive' which means needs, desires, wants or drives within the individuals. Beside, inspiration is a feeling of enthusiasm you get from someone or something, that gives you new ideas such as idol. Inspiration also can define as a process that encourages or stimulates the mind to do something especially creative. It is mentally stimulated to take action after seeing or learning something around. Inspiration is different from motivation, which is the process that motivates or influences a person to achieve what they want. While inspiration is a creative idea that comes from within after a stimulus from the outside. But inspiration can motivate a person to reach their goals. Developed economies need a creative community for national development. Therefore, students play a key role in achieving this goal. As a result, inspiration and motivation can help students make the right choices, especially for their studys. They will be smarter in managing their free time to achieve a better future